2012
DOI: 10.1109/tsg.2012.2194518
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Based Smart Power System, Part I: Design and System Development

Abstract: This paper presents the design and development of a hardware-based laboratory smart grid test-bed. This system is developed at the Energy Systems Research Laboratory, Florida International University. The hardware/software based system includes implementation of control strategies for generating stations, and power transfer to programmable loads in a laboratory scale of up to 35 kilowatts in ac power and 36 kW in renewable sources and energy storages. Appropriate software was developed to monitor all system pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(72 citation statements)
references
References 30 publications
(18 reference statements)
0
68
0
1
Order By: Relevance
“…Our review of the existing modern power laboratories shows a number of developments related to: a) smart grid laboratories [13][14][15][16][17][18][19][20] b) renewable energy laboratories [15,21,22] c) SCADA (Supervisory Control And Data Acquisition) integrated laboratories [14,22,23] d) remote power laboratories [21,22,24] The list above shows that power engineering is becoming multidisciplinary field and the laboratories developed for teaching power engineering can be used in other areas including, communication, computer science, artificial intelligence, SCADA security, etc. Having this in mind can help academic staff teaching power engineering justify investment into these laboratories as they can be used by broader teaching and research communities especially when they are shared online by different departments of the university and different universities.…”
Section: Modern Electrical Power Laboratoriesmentioning
confidence: 99%
“…Our review of the existing modern power laboratories shows a number of developments related to: a) smart grid laboratories [13][14][15][16][17][18][19][20] b) renewable energy laboratories [15,21,22] c) SCADA (Supervisory Control And Data Acquisition) integrated laboratories [14,22,23] d) remote power laboratories [21,22,24] The list above shows that power engineering is becoming multidisciplinary field and the laboratories developed for teaching power engineering can be used in other areas including, communication, computer science, artificial intelligence, SCADA security, etc. Having this in mind can help academic staff teaching power engineering justify investment into these laboratories as they can be used by broader teaching and research communities especially when they are shared online by different departments of the university and different universities.…”
Section: Modern Electrical Power Laboratoriesmentioning
confidence: 99%
“…New generation testbeds are designed and implemented using actual power system control equipment interfaced with actual grid and/or simulation software to allow replication of full-scale cyber-physical system performance at a large laboratory scale. Several papers addressed the development of the power system cyber-physical testbeds [5][6][7][8][9][10][11][12][13][14][15][16][17]. In [5][6][7][8][9], concept of end to end testing using the system in-the-loop (SIL) testbed is presented.…”
Section: Introductionmentioning
confidence: 99%
“…In [5][6][7][8][9], concept of end to end testing using the system in-the-loop (SIL) testbed is presented. In [10][11][12][13][14][15], hardware-in-the-loop (HIL) testing platforms for different studies including distributed generation and power electronic interfaces are discussed. Examples of cyber-physical testbeds to study different concerns related to power system cyberattacks can be found in [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The smart grid testbed is implemented by the efforts of a group of students [59], [60], however, the author of this dissertation is solely responsible for all the aspects related to the DC microgrid design, control and implementation, as well as the aspects related to the interaction between AC and DC and the ideas of how the energy available from renewable energy can be used to solve operational problems on the AC side.…”
Section: Fcmentioning
confidence: 99%